(untitled) (Minerva, 2021)
This work offers a general presentation on De nuptiis Philologiae et Mercurii, its latest book and its author, Martianus Capella. The text is an allegorical and encyclopedic work from late Latinity. The focus of the study will be on Epigraphs 922-929. In them, the author shows the nature of music, its benefits and effects on humankind, animals, and inanimate beings. They also include a speech on the origins of music and some exempla on its universal and magical power. These exempla and mirabilia will be analysed and compared to other sources, noting their peculiarities, similarities and / or discrepancies.